Explaining the Role of Geopolitical Components Affecting spatial planning of border regions (Case Study: West Azarbaijan Province) - Ahmad Aftab; Ali Majnoony; Akbar Houshmand (تحقیقات کاربردی علوم جغرافیایی)
The present study aims at identifying geopolitical components affecting the spatial planning of border regions in the East Azarbaijan province. The research is an applied research that has been carried out using statistical tests, path analysis and Promethean decision making model. The results of the research showed that social variables with r = 0.811, r = 0.662, political, r = 0.851, ranked first to third. The results of path analysis also showed that political components with 0.96, social and cultural components with 0.93 and economic components with 0.36, have a direct effect on the realization of eastern Azarbaijan province boundaries. Finally, the results of the Prometheus model showed that Sardasht, Maku, Oshnaviyeh, Piranshahr, Orumiyeh, Salmas, Khoy, Siah Cheshmeh and Sardasht, respectively, are in the first to the nineteenth priorities. Therefore, according to the findings of the research, it is suggested that security and security measures are implemented with economic, political, and socio-cultural approaches.